Investigating Green Purchase Decission of SMEs in Development Counties: A Literature Review - Yoga Religia; Budi Purnomo Saputro; Al Virizky Arjunitha Al Munawir (AIBPM Publisher, 2024)
This study investigates factors influencing green product purchasing by Small and Medium Enterprises (SMEs) in developing countries, focusing on the Theory of Consumption Values (TCV) and the Theory of Planned Behavior (TPB). Using a systematic literature review, articles published between 2020 and 2024 were analyzed. Findings show that TCV is crucial for understanding green purchasing behavior through functional, social, emotional, and epistemic values, significantly impacting consumer intentions. Consumers prefer products that meet functional needs and align with their values. TPB highlights attitudes, subjective norms, and perceived behavioral control in shaping purchase intentions. Positive environmental attitudes, social support, and perceived control encourage green product purchasing. Integrating TCV and TPB offers a comprehensive understanding of the dynamics influencing these decisions. Practically, this study guides marketers in developing effective green marketing strategies by highlighting product benefits and leveraging community support. Although focused on recent literature and TCV and TPB, further research could explore other factors influencing green purchasing in different contexts. This study enriches the literature on green purchasing and supports sustainable economic growth for SMEs in developing countries.